Insights into interface and bulk defects in a high efficiency kesterite-based device. Issue 1 (11th January 2021) - Fonoll-Rubio, Robert; Andrade-Arvizu, Jacob; Blanco-Portals, Javier; Becerril-Romero, Ignacio; Guc, Maxim; Saucedo, Edgardo; Peiró, Francesca; Calvo-Barrio, Lorenzo; Ritzer, Maurizio; Schnohr, Claudia S.; Placidi, Marcel; Estradé, Sònia; et al.
Abstract : Example of an advanced characterization study of a complex system (thin film solar cell) that may serve as an instructive handbook to help building up the full picture of multilayer-based devices for a broad spectrum of readers and researchers. Abstract : This work provides a detailed analysis of a high efficiency Cu2 ZnSnSe4 device using a combination of advanced electron microscopy and spectroscopy techniques. In particular, a full picture of the different defects present at the interfaces of the device and in the bulk of the absorber is achieved through the combination of high resolution electron microscopy techniques with Raman, X-ray fluorescence and Auger spectroscopy measurements at the macro, micro and nano scales. The simultaneous investigation of the bulk and the interfaces allows assessing the impact of the defects found in each part of the device on its performance. Despite a good crystalline quality and homogeneous composition in the bulk, this work reports, for the first time, direct evidence of twinning defects in the bulk, of micro and nano-voids at the back interface and of grain-to-grain non-uniformities and dislocation defects at the front interface. These, together with other issues observed such as strong absorber thickness variations and a bilayer structure with small grains at the bottom, are shown to be the main factors limiting the performance of CZTSe devices. These results open the way to the identification of new solutions to further developing the kesterite technology and pushing it towards higher performances. Moreover, this study provides an example of how the advanced characterization of emergent multilayer-based devices can be employed to elucidate their main limitations.